PREPARATION AND CHARACTERIZATION OF ADSORBENT FROM WASTE SHEA (Vitellaria paradoxa) NUT SHELL (FUDMA JOURNAL OF SCIENCES, 2024)
The activated carbons (adsorbents) prepared in this study, were from Vitellaria paradoxa nut shell following the two steps of carbonization and activation processes using H3PO4 and KOH as activating agents and were labelled as HVP for H3PO4 modified adsorbent and KVP for KOH modified adsorbent. The activated carbons were characterized using standard methods of analysis. Bulk density (g/cm3) of the carbons (HVP and KVP) were 0.72±0.03 and 0.69±0.05, and attrition (%) values of 40.76±0.16 and 42.37±0.23 were obtained for HVP and KVP respectively. Results obtained also depict the presence of carboxyl O-H and C-O groups, and the N-H of amine on the surfaces of the activated carbons. The values of pH point of charge zero (pHzpc) obtained for HVP and KVP were 6.40 and 6.60 and were less than the pH values of 6.78±0.00 and 7.18±0.01 for HVP and KVP respectively. SEM results revealed surfaces with pores with different dimensions in both HVP and KVP. Results of the study suggest that the prepared adsorbents can be effectively applied in wastewater treatment.
Keywords: Adsorbent; Agricultural wastes; Porosity; Bulk density; Wastewater